Mo Yan in Context Nobel Laureate and Global Storyteller - Duran, Angelica (Comparative Cultural Studies, 2014)
This is the first English-language study of the Chinese writer's work and influence, featuring essays from scholars in a range of disciplines, from both China and the United States. Its introduction, twelve articles, and epilogue aim to deepen and widen critical discussions of both a specific literary author and the globalization of Chinese literature more generally.The book takes the "root-seeking" movement with which Mo Yan's works are associated as a metaphor for its organizational structure. The four articles of "Part I: Leaves" focus on Mo Yan's works as world literature, exploring the long shadow his works have cast globally.